Caring for creative possibility: locality as heritage - Wiórko, Agata (2021)
This paper addresses the problem of how to articulate the notions of heritage and locality, while looking at accessible public space as the ground for the awareness of its possibilities. Acknowledging the importance of scattered creative and co-creative experiments - spatial and political practices which are seen as proposals with great cultural value -what is proposed is a challenge: to look at neighborhoods as players in a more densely connected urban narrative. The way heritage is reinterpreted appears then as a citizenly contribution for a more diverse urban sensescape, where values such as vicinity or provocation can become operative. A major conclusion is that an ethics of the curatorial - as implied in the concept by Irit Rogoff - is the basis for a pragmatics of the urban realm where heritage can have a futurant sense.